Characterization of unsaturated tropical soil site by in situ tests - Rocha, B. P.; Dos Santos, R. A.; Bezerra, R. C. [UNESP]; Rodrigues, R. A. [UNESP]; Giacheti, H. L. [UNESP] (My University, 2016)
Geotechnical site characterization consists in determining the stratigraphical profile, the groundwater level and the estimative of geo-mechanical designs parameters required for each project. In situ tests techniques can offer the best available and most economical way to achieve this characterization for different site conditions. This paper presents and discusses CPT, DMT, seismic (down-hole) and laboratory tests carried out in an unsaturated tropical sandy soil site, which the top 13 m is a colluvium overlaying a residual soil from sandstone. The results showed that the CPT and DMT tests were efficient for detailed stratigraphic logging, estimative of geotechnical parameters, however, temporal variability should be considered for proper site characterization of unsaturated tropical soils.